Digital storytelling: a systematic review - Nur Fatin Nabila Abd Rahman; Rofiza Aboo Bakar (Journal of English Language Teaching Innovations and Materials (Jeltim), 2020)
Digital storytelling (DST) is one of the helpful educational tools in the teaching and learning process. Nonetheless, there is a scarcity of systematic reviews to enlighten how it was applied and what was done in this area. This paper performed a systematic review of five articles on using DST to foster English speaking skills among learners.  This research established continuous interest in the background of South-East Asian countries, including learners at the pre-school till tertiary education levels.  DST has been used in the humanities and social sciences as either a stand-alone teaching or in conjunction with other teaching techniques. The review classified two directions (ideal and reflective) as well as six outcomes: affective, intellectual, educational, technical, linguistics, and communal. Hence, this study synthesizes and discusses further two issues: affective motivating passion and a creative, imaginative, and resourceful platform. It is hoped this study able to discuss potential explanations for these issues and offer insights for future studies.